Sexual reproduction by Neurospora in nature - Alka Pandit; Ramesh Maheshwari (Fungal Genetics Reports, 1994)
Except for a solitary report on the presence of perithecia of Neurospora on pine trees burned in the fire which followed an earthquake in Tokyo (Kitazima 1925 Ann. Phytopath. Soc. Japan 1:15-19), all other attempts to find the sexual stage in nature were unsuccessful (Shear and Dodge 1927 J. Agric. Res. 34:1019-1024; Prakash 1965 Neurospora Newsl. 7:5-6; Shaw 1990 The Mycologist 4:6-13). However, based on the available information on the population structure of Neurospora, Perkins and Turner (1988 Exp. Mycol. 12:91-131) predicted that sexual reproduction is prevalent in nature.